Hubungan Penggunaan Face Mist Berbahan Dasar Alami terhadap Kesehatan Kulit Wajah Pada Cuaca Ekstrem Di Kalangan Masyarakat Kabupaten Jombang - Anjarsari, Desy Siswi; Imaningsih, Agustin Nur; Arviani, Indi; Prasetyo, Achmad Yogi (Innovative: Journal Of Social Science Research, 2025)
Increasing global temperatures trigger the emergence of more intense extreme weather which has negative impacts, one of which is causing skin problems. In Indonesia, the prevalence of acne among teenagers is quite high, ranging between 80-85%. Method: This research uses quantitative correlational methods, with data analysis using the Spearman Rank correlation test. The sample was taken through random sampling of 95 respondents. Data collection was carried out using a structured questionnaire. Results: A significance value of 0.000 (< 0.05) shows that there is a significant relationship between perceptions of facial skin health in extreme weather and interest in using natural-based face mist in Jombang Regency. The strength of the relationship between variables is 0.503, which is included in the sufficient category. Discussion: The direction of the positive relationship in the Spearman rank correlation test shows that the higher the public's perception of the importance of caring for facial skin health in extreme weather, the higher their interest in using natural face mist. Conclusion: There is a significant and positive correlation between people's understanding of facial skin health in extreme weather and their desire to use natural face mist products. Keywords: Extreme Weather, Face Mist, Skin Health.